KEPASTIAN HUKUM TERHADAP TENAGA KERJA PKWT YANG DIPEKERJAKAN KEMBALI SETALAH 5 TAHUN MASA KONTRAK BERDASARKAN PERATURAN PEMERINTAH NOMOR 35 TAHUN 2021 - asep gunawan (CV Rewang Rencang, 2024)
Law Number 13 of 2003 concerning Labor Regulations delineates the contractual periodization for Specific Time Work Agreements (PKWT), initially constraining the temporal interval to a maximum of 3 (three) years. Subsequently, the Job Creation Law, through its regulatory derivative Governmental Regulation Number 35 of 2021, expands the contractual duration to a maximum of 5 (five) years. However, this normative construction is critically viewed as generating detrimental implications for workers, stemming from the ambiguity surrounding the mechanisms for obtaining Indefinite Time Work Agreements (PKWT). This regulatory condition is perceived as systematically eroding juridical protections for labor resources while simultaneously advantaging employers. The research aims to conduct a comprehensive examination of legal certainty pertaining to PKWT workers who are re-employed after the 5-year contract period, based on Governmental Regulation Number 35 of 2021, and to explore the instrumental role of governmental entities in the mechanism of transforming PKWT status to PKWTT within the domain of labor law practices. This study employs a normative juridical research methodology, conducted through systematic exploration of bibliographic sources or secondary data as an investigative foundation. The research involves a comprehensive examination of regulations and literature correlated with the investigated problematic domain. The legal sources utilized in the research encompass primary, secondary, and tertiary legal materials. Data collection strategies incorporate two complementary approaches: comprehensive bibliographic investigation and field research, which includes observational and interview methodologies at the designated research site. Moreover, the applied data analysis technique is qualitative in nature a descriptive-analytical approach that references specific research problems, subsequently correlating them with academic literature, expert legal perspectives, and existing legislative frameworks. Following the enactment of the Job Creation Law, the regulatory framework for renewing specific-term employment agreements (PKWT) has undergone substantial modifications. The remaining provisions are exclusively concentrated on the mechanisms governing PKWT extensions. Referencing Government Regulation Number 35 of 2021 concerning Specific-Term Employment Agreements, Outsourcing, Working Hours and Rest Periods, and Termination of Employment—which represents a derivative instrument of the Substitute Government Regulation Number 02 of 2022 regarding Job Creation—a definitive clarification emerges, highlighting the significant procedural challenges confronting contracted workers in transitioning to permanent employment status.